A review of STATCOM control for stability enhancement of power systems with wind/PV penetration: Existing research and future scope. (28th August 2021) - Sadiq, Rehan; Wang, Zhen; Chung, C.Y.; Zhou, Changping; Wang, Chenxuan
Abstract: In recent years, the development of renewable energy sources (RESs) and their integration with the conventional power network have increased significantly. Due to the power grid transformation brought about by the large penetration of power electronics converter‐based RESs such as wind and solar photovoltaic (PV), the operation and control of the interconnected power system has become a challenging task with respect to sustaining its stability and reliability. Power systems are confronted by several new stability issues because the dynamic behavior of converter‐interfaced renewable sources differs from conventional generation. In this respect, static synchronous compensator (STATCOM), a shunt connected flexible AC transmission system (FACTS), is recognized as a fundamental solution for maintaining power system stability. This paper presents a thorough and state‐of‐the‐art review of STATCOM control in wind‐ and/or PV‐interfaced power systems for enhancing system performance by addressing key stability issues related to rotor angle stability, voltage stability, and resonance stability. A comprehensive analysis of various control techniques of STATCOM based on conventional, adaptive, nonlinear, predictive, robust, and coordinated control and soft computing techniques is provided. Furthermore, the function of the grid‐side converter of the wind/PV plant as a STATCOM is also evaluated. Finally, the shortcomings of existing research are highlighted, current control challenges are presented, and several topics for future research are suggested. This paper provides researchers the opportunity to consider the current state of research and develop new control schemes for STATCOM to further improve the stability of modern power grids. Abstract : Review of various control strategies of STATCOM is presented for stability enhancement of wind/PV penetrated power system by addressing the key stability issues related to rotor angle stability, voltage stability and resonance stability. Moreover, present control challenges are highlighted along with some future recommendations.